Мусорщик: роман / А. Константинов, А. Новиков - Константинов Андрей Дмитриевич (Русский проект, 2001)
Экземпляры: ф.16 (2002) / Инвентарный номер: 43754 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44